Investigation of Decolouration Thermodynamics and Kinetics of Acid Brilliant Scarlet GB on Expanded Graphite Loaded with Titania - Pang, Xiu-Yan; Wei, Chen; Lin, Rui-Nian (Asian Journal of Chemistry, 2011)
To study thermodynamic and kinetic characteristics of Acid Brilliant Scarlet GB decolouration on expanded graphite loaded with titania (EG), expanded graphite was prepared firstly with 50 mesh natural graphite as raw materials, potassium permanganate as oxidant, vitriol and tetra n-butyl titanate as intercalation compound. Then it was charactered with XRD and micromeritics instrument. The influence of decolouration time, adsorbate initial concentration, ionic strength and temperature on decolouration rate was detected. Based on pseudo first-order and secondorder kinetic model, the decolouration model was discussed. Decolouration rate and activation energy were calculated. Studies show that decolouration rate of Acid Brilliant Scarlet GB on expanded graphite decrease with the increase of the adsorbate initial concentration and increase with the increase of ionic strength. The decolouration process can be well described by the pseudo second-order kinetic model. The decolouration equilibrium time and half decolouration time decrease with the increase of temperature and adsorption of expanded graphite is the main factor of decolouration.